Metode Reward and Punishment sebagai Basis Peningkatan Kedisiplinan Siswa Madrasah Diniyyah - Abdul Rosyid; Siti Wahyuni (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
Discipline character has a significant role in shaping the personality of students. In the context of learning, the discipline also has a relationship with the process of teaching and learning activities because it is one of the important factors that encourage student achievement. This paper discusses the form and implementation of reward and punishment that applies at Madrasah Diniyyah Al-Mahrusiyyah Putra as a way to shape the character of students' discipline and the basis for improving their learning achievement. The results of this study found that the forms of rewards given were various, including; gave several awards, prizes, and certificates of appreciation for students who passed the Nadzam festival, the best Nadzam class, exemplary students, and also given to other outstanding students. The forms of punishment given include giving punishments in the form of reprimands and advice, squatting, crossing for students who are late, giving red cards to students whose average test scores are low, giving punishments for a little physical contact, physical punishment for students who often do not get paid. In addition, breaking the rules and being undisciplined. The various forms of application of rewards and punishments that are given in stages according to the level and frequency of mistakes made show that disciplinary problems can be resolved properly and impact learning achievement because the process of teaching and learning activities becomes more optimal and orderly.